Impact of CELIK CPR training on knowledge, attitude and self-confidence among pre-service teachers - Muhamad Nur Fariduddin; Siau, Ching Sin; Tee, JN (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Cardiopulmonary resuscitation (CPR) training among school teachers are well known and teachers should be trained well. Meanwhile, Malaysia has yet to galvanise our educators to move towards CPR training. This study aimed to investigate the efficacy of implementing the CELIK CPR handbook of CPR training to enhance the knowledge, attitude and self-confidence in performing CPR among pre-service teachers in Malaysia. A quasi-experimental study was implemented involving 20 pre-service teachers from the Department of Physical & Health, Faculty of Education, Universiti Teknologi MARA. Multiple-choice questions and questionnaires to assess the knowledge, attitude and self-confidence of the respondents were used before (week-2) and after (week-14) CPR training. A total of 5 (25%) pre-service teachers successfully achieved the passing scores of χ2(1, N = 20) = 5.71; p<0.05 with post-knowledge scores, 5.40, 95% CI (-7.16, -3.64), which was significantly higher compared to the pre-scores, t(19) = -6.421; p<0.001, with large effect size, d = 1.76. However, there were non-statistically significant differences for attitude, t(19) = -0.765; p>0.05 and self-confidence, t(19) = 0.00; p>0.05. Pre-service teachers had limited knowledge, low self-confidence and attitude about CPR. Early training is crucial as pre-service teachers constitute an important potential for CPR training dissemination among school children and the public.